Characteristics, management, and outcomes of segmental and subsegmental pulmonary embolism in ICU patients: A retrospective cohort study - Nuanprae Kitisin; Nattaya Raykateeraroj; Yukiko Hikasa; Jonathan Nübel; Alessandro Caroli; Glenn Eastwood; Emily Harman; Sandra Lussier; Derick Adigbli; Jane E. Lewis; Numan Kutaiba; Daryl Jones; et al. (PLoS ONE, 2026)
Objective To describe the incidence, management, and outcomes of segmental and subsegmental pulmonary embolism (PE) in intensive care unit (ICU) patients and to explore associations between therapeutic-dose anticoagulation and clinical outcomes. Design Single-center retrospective cohort study. Setting Tertiary academic hospital ICU between January 2019 and June 2025. Patients Critically ill adults (≥18 years) who underwent computed tomography pulmonary angiography (CTPA) during ICU admission and had radiologically confirmed segmental or subsegmental PE. Interventions None. Measurements and main results Radiology reports of all CTPA examinations performed in ICU-admitted patients were screened to identify the most proximal level of thrombus. Clinical records were reviewed for demographics, illness severity, radiologic characteristics, anticoagulation practice, bleeding, venous thromboembolism (VTE) recurrence, and mortality. Among 896 CTPA examinations performed in 804 patients, 164 examinations (18.3%) identified PE. Of these, 115 scans (12.8% of all CTPAs) demonstrated distal PE only, corresponding to 104 patients (12.9%) (61 segmental, 43 subsegmental). Overall, 96% of patients with distal PE received anticoagulation and 86% of anticoagulated patients received therapeutic-dose regimens. Bleeding occurred in 15% (major bleeding 12%), 90-day VTE recurrence in 7.8%, and 90-day mortality in 24%. No statistically significant association was found between the use of therapeutic-dose anticoagulation and 90-day mortality (adjusted odds ratio [OR], 0.70; 95% CI, 0.21–2.45), bleeding episodes (adjusted OR, 2.34; 95% CI, 0.47–19.2), or VTE recurrence (adjusted OR, 0.69; 95% CI, 0.11–6.22). Conclusions In critically ill adults, segmental and subsegmental PE are commonly detected on CTPA and are usually treated with therapeutic-dose anticoagulation. Although VTE recurrence was less frequent than bleeding episodes and mortality, our study did not find a significant association between therapeutic-dose anticoagulation and bleeding episodes, recurrent VTE, or mortality. Larger prospective studies are needed to define optimal anticoagulation strategies for ICU patients with distal PE.